Election Night: Karen Humphrey Elected Mayor of Fresno - Watkins, Howard::::::::: (1989)
Karen Humphrey speaking at microphone with ? And Bob Lincon with her "Karen Humphrey for Mayor" yard signs and red, white and blue décor on wall